The Negative Impact of Monodisciplinary Tradition in Arabic Language and Literature Studies - Sukron Kamil (Buletin Al-Turas, 2022)
PurposeAs the title suggests, this paper discussed the monodisciplinary tradition of studying Arabic language and literature which became an obstacle for scientific publications or other dissemination activities.MethodThe qualitative study made a library research design whose primary data sourced from journal articles, books, research proposals/thesis, and online sources. Careful reading and analysis were applied to get the intended data useful in answering the problems being investigated. The collected data and relevant information were qualitatively analyzed using Ricoeur’s Hermeneutics.Results/FindingsThe found out many negative consequences of the using of a monodisciplinary study. In general, the study of Arabic language and literature had lack of research significance, depth of analysis, and criticism. It was neither lack of originality nor creativity. In addition to the mono-disciplinary study tradition factor, the teaching university paradigm and poor learning traditions became another contributing factor.ConclusionA mono-disciplinary in studying Arabic language and literature did not contribute significantly to its development. It was necessary to use multidisciplinary intra/interdisciplinary paradigm as a trend in the teaching and studying of Arabic language and literature in the world by which various shortcomings lessened.